Systematic Review for Leisure: The Factors Affecting the Leisure - Zarotis, George F.; Tokarski, Walter (New Ideas Concerning Arts and Social Studies Vol. 2, 2025)
In the 1950s and 1960s, most of the time, almost like the proposition hiding behind this, it was set as a basis that leisure can be explained by a number of defined variables. These so-called determinant ideas initially recognised that knowledge of only very few variables, most often Sociodemographic, was sufficient to define and explain leisure. Leisure cannot be perceived as a phenomenon that affects all people to the same degree. General statistical trends such as more time, higher available disposable income or technical innovations cannot lead to the conclusion that every member of the society changes their leisure activities in the same way and adapts to the new framework conditions. Whether and how individual social differences affect leisure time, are reproduced or transformed in view of current socio-political changes, continues to be a particularly topical question in the study of leisure time and lifestyle. The ultimate goal of this research is the analysis of behavioural factors, the course of life and lifestyle as regards leisure time. The method adopted for the study was a review of the relevant literature. The present study is a bibliographical survey study that presents the critical points of existing knowledge about a theoretical approach. The review of the current study refers to clearly formulated questions and uses systematic and explicit criteria for the critical analysis of a published paper by summarising, sorting, grouping and comparing. In the light of the present study, it is found that a differentiated view of leisure behaviour should essentially be followed from two complementary perspectives: a theory of action and a theory of structure. This action occurs in a social structure, which specifies a place of action for the individual, in which the individual's actions are consciously or unconsciously adapted. The analysis of social structures to date can be made more precise. Lifestyles are mainly distinguished by the activities they contain. This means creating a style that results from everyday visible actions and ways of behaving. Orientations are also taken into consideration, which could lead to the conclusion on which principles people organise their lives. Lifestyle, in a nutshell, can be understood as a thematically structured model of providing motivation, perceptions, behaviour and experience in order to meet needs, accomplish tasks, and reach or achieve goals. Leisure time behaviour is the broader concept of individual aspects such as activities or actions during leisure time, the shaping of leisure time and the model of leisure time. Leisure time activities are, therefore, characteristic measures of the socially acceptable range of behaviours in a society, class, or group with respect to leisure. Examination of leisure time biographies shows that leisure time activities and patterns change significantly over the course of life. From the social sciences point of view, it has been shown that lifestyle expression depends on demographic factors that are not influenced, such as age and gender, as well as social factors such as education, occupational status and income. As a result, it can be maintained that the changing trends as regards leisure time that were discussed here undoubtedly provide a good basis for estimating leisure activities. Adequate time and financial resources are essential to this end. On the contrary, it is also accepted that lifestyles should not be regarded only as dependent variables, but could also serve as declarative dimensions.